2002
DOI: 10.1152/japplphysiol.00756.2001
|View full text |Cite
|
Sign up to set email alerts
|

Silver ions induce Ca2+release from the SR in vitro by acting on the Ca2+release channel and the Ca2+pump

Abstract: release channel (CRC), causing the channel to open. To further examine the effects of AgNO 3 on the CRC and the Ca 2ϩ -ATPase, Ca 2ϩ release was measured in muscle homogenates prepared from rat hindlimb muscle using indo 1. Cyclopiazonic acid (CPA) and ruthenium red (RR) were used to inhibit the Ca 2ϩ -ATPase and block the CRC, respectively, before inducing Ca 2ϩ release with both AgNO3 and 4-chlorom-cresol (4-CMC), a releasing agent specific for the CRC. With AgNO3 and CPA, the early rapid rate of release (ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 43 publications
1
61
1
Order By: Relevance
“…We have followed the procedure used by Ruell et al (31), in which AgNO 3 is used as the releasing agent. In recent work, we have found that, unlike 4-chloro-m-cresol, which is specific to the Ca 2ϩ -release channel, AgNO 3 can also act on the Ca 2ϩ -ATPase and can lead to reversal of the pump action (39). Moreover, because Ca 2ϩ release occurs in two phases, training effects may be different between the phases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have followed the procedure used by Ruell et al (31), in which AgNO 3 is used as the releasing agent. In recent work, we have found that, unlike 4-chloro-m-cresol, which is specific to the Ca 2ϩ -release channel, AgNO 3 can also act on the Ca 2ϩ -ATPase and can lead to reversal of the pump action (39). Moreover, because Ca 2ϩ release occurs in two phases, training effects may be different between the phases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because Ca 2ϩ release occurs in two phases, training effects may be different between the phases. This study was completed before our examination of the Ca 2ϩ -release kinetics using different releasing agents (39). As such, we have followed the popular practice of using the second phase of Ca 2ϩ release and the releasing agent AgNO 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Oxalate-supported SR Ca 2+ uptake rate was assessed in RV muscle homogenates using the fluorescent dye Indo-1 and a spectrofluorometer equipped with dual-emission monochromators and was normalized for total protein concentration (Tupling and Green, 2002). SERCA activity was assessed via an enzymecoupled assay in crude homogenates prepared from RV muscles in the presence (without ionophore A23187) or absence (with 4 mM ionophore A23187) of a Ca 2+ gradient using a spectrophotometric plate reader assay which has been described previously (Duhamel et al, 2007).…”
Section: Serca Ca 2+ Uptake and Ca 2+ -Atpase Activitymentioning
confidence: 99%
“…Differentiating the linear-fit curves allows determination of Ca 2ϩ release rates. Phase 1 Ca 2ϩ release is characterized by a rapid early release (ϳ0 -2 s), whereas phase 2 Ca 2ϩ release is characterized as the slower, more delayed release (ϳ5-15 s) (13,49).…”
Section: Participantsmentioning
confidence: 99%